The Impact of Good Governance on Economic Development in India: A Comprehensive Study (Multitech Journal of Applied Sciences (MJAS), 2025)
This research explores a crucial link between good governance and building a better world. We find that when governments are honest, transparent, and fair, and allow people to have a say in decisions, it leads to amazing results. Countries with strong governance often experience better economies, happier people, and more peaceful societies. We examine real-life examples from different parts of the world to show how good governance makes a difference. But we also discover that creating and maintaining good governance is not easy. We have to overcome challenges like leaders who are unwilling to change, weak government systems, social divisions, and economic problems. This research calls for a collective effort to make good governance a reality. We need to find innovative solutions, empower citizens to participate in decision-making, and raise awareness about the importance of good governance. Ultimately, this research emphasizes the urgent need to work together to make good governance a cornerstone for a brighter future, where everyone has a chance to live a better life
Keywords: Development, Good Governance, Economic Stability, Brighter Future, Empower Citizens